Desarrollo de competencias comunicativas en niños de transición fundamentado en la mediación didáctica del cuento (2021)
Improving educational quality is not an easy task for any country; since the progress and development of nations is based on it; But the most worrying thing for the purposes of this research is that children's communication skills represent an entry base for scientific knowledge, and for educational processes. From this scenario, the purpose of this research is to analyze the development of communication skills in transitional children from the didactic mediation of the story. The approach to the research problem is determined by the contributions of the deductive rationalist epistemological approach, in correspondence with a mixed paradigm that is operationalized from a qualitative-quantitative design organized into a theoretical-documentary component and an empirical-field component. For these purposes, the research identifies two populations: One made up of preschool teachers who constitute the first unit of analysis, to which a 16-item questionnaire is applied on the development of communicative competence in transitional children; and another population that are children, who constitute the second unit of analysis, from the annotations made of their behaviors, and registered in the Valuation Register instrument, where the didactic mediation of the teacher and the development of their communication skills are evidenced. Among the main results is the scarce permanent teacher training; improvisation in curriculum planning; little motivation and interest in improving educational practices; and the absence of a relevant pedagogical strategy for the development of communication skills.